Smallholder farmer insights on information systems: current use and future needs in the Eastern Gangetic Plains - Karki, Emma S.; Karmacharya, Saurya; Ghosh, Arunava; Rana, Gunjan; Chakma, Kali Ratan; Timsina, Pragya; Chaudhary, Anjana; Nandi, Ravi (Informa UK Limited, 2025)
Purpose: The Eastern Gangetic Plains (EGP) region is characterized by resource-poor smallholder farmers, high dependence on agriculture, poor market infrastructure, limited access to new technologies, and frequent climate aberrations. These challenges underscore the need for a robust agricultural information system to enhance food security and agricultural productivity. Methodology/Approach: This study examines current access to existing information channels and identifies preferences for future information delivery and dissemination mechanisms from the perspective of small holder farmers in the Eastern Gangetic Plains (EGP) through empirical data collected from 1,440 households in India, Nepal and Bangladesh. Findings: Results from all locations indicate (i) heavy reliance on informal sources like agrovets and village peers in the absence of a robust extension system, (ii) strong preference for more formal, government-driven information sources (iii) need for a pluralistic approach to information dissemination, integrating public, private, and community-based sources to meet diverse farmer needs and (iv) training was the most preferred method of information dissemination. Practical implications: The results advocate for policy changes and the development of inclusive, innovative extension systems to better serve smallholder farmers, ensuring improved access to valuable information and fostering agricultural development in the EGP. Theoretical implications: This study contributes to the literature on farmer's current and future preferences for both agricultural and off-farm activities in the EGP highlighting the role of pluralistic agriculture extension. Value: This paper addresses a gap in literature by examining the perceptions of smallholder farmers on their current and future information sources for agricultural and off-farm activities in the EGP, a region that lacks literature regarding information systems.